Dopełnienie zbioru rozmytego względem argumentu - Dworniczak, Piotr (Investigationes Linguisticae, 2011)
In the paper the concept of complements in the fuzzy envi-ronment is presented. The complements are considered in two variants; the complement to the universum and the complement with respect to the argument. The definitions of both form of complements are given. The basic proper-ties of the complements with respect to the argument, rare-ly noted in the literature, are presented. The simple inter-pretation of the complement with respect to the argument in the modeling of linguistic variables and their antonyms has been proposed.